Apathy as a treatment target in neurocognitive disorders: Clinical trial implications. (31st December 2021) - Mortby, Moyra E; Adler, Lawrence; Agüera‐Ortiz, Luis; Bateman, Dan R; Brodaty, Henry; Cantillon, Marc; Geda, Yonas E.; Ismail, Zahinoor; Lanctôt, Krista L.; Marshall, Gad A; Padala, Prasad R; Politis, Antonis; et al.
Abstract: Background: Apathy is the most prevalent, stable and persistent neuropsychiatric symptom observed across the neurocognitive disorders spectrum and is linked to poorer disease outcome, reduced daily functioning and higher levels of caregiver distress, and an increased risk of mortality. Recent advances in understanding of phenomenology, neurobiology and intervention trials highlight an increased interest in and recognition of apathy as an important target for clinical intervention. We therefore conducted a comprehensive review and critical evaluation of recent advances to determine evidence‐based suggestions for future trial designs. Method: A critical review of latest research on apathy as a treatment target in pre‐dementia and dementia populations by the Alzheimer's Association International Society to Advance Alzheimer's Research and Treatment (ISTAART) Neuropsychiatric Syndromes Professional Interest Area (NPS‐PIA) Apathy Workgroup. This review focused on 4 key areas: 1) mechanisms and biomarkers; 2) assessment; 3) treatment and intervention efficacy; and 4) pre‐dementia states. Result: Considerable progress has been made in understanding apathy as a treatment target and appreciating pharmacological and non‐pharmacological apathy treatment interventions. Areas of the literature requiring greater investigation include: diagnostic procedures, symptom measurement, understanding the biological mechanisms and biomarkers of apathy, and a carefully considered and well‐formed approach to the development of treatment strategies. Conclusion: We have made much progress in better understanding the role of apathy in affecting the impact and course of neurocognitive disorders and are starting to see some successes in targeting new treatments. To advance the recognition of apathy as a treatment target for clinical trials, it is essential that a better understanding of the subdomains and biological mechanisms of apathy are achieved. We propose the utility of a comprehensive multi‐national longitudinal observational study of neuropsychiatric symptoms in which the study of apathy is incorporated.